Gender, school location and primary school pupils environmental knowledge in Oyo township (2013)
The paper examines the influence of gender and school location on pupils’ environmental knowledge. An ex post facto research was adopted and Environmental Knowledge Test was administered to 264 (139 male and 125 female) primary five pupils from 12 public primary schools purposively selected from Atiba, Afijio, Oyo West and Oyo East Local Government Areas of Oyo Metropolis of Oyo State. The results as obtained from ANOVA show that school location and gender had no significant effect, on pupils’ environmental knowledge. These findings have implications for government and teachers who are the stakeholders in the educational sector.